2018
DOI: 10.1515/multi-2015-0103
|View full text |Cite
|
Sign up to set email alerts
|

Multilingualism, urban change and gentrification in the landscape of a Brussels neighbourhood

Abstract: This paper focuses on how different historical stages of socio-economic development in Brussels are played out on the ground over time in one particular inner-city neighbourhood, the Quartier Dansaert. In particular, I document the history of this neighbourhood and how urban change and gentrification have impacted the outlook of multilingualism and the development of multilingual discourses and language hierarchies in its material and semiotic landscape over time. By using the rich history of multilingualism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…These samples originally intended to analyse the presence of different ethnic minority groups in the territory. However, data suggested that the LC might not have only recorded traces of multilingualism, but also traces of the complex process of gentrification, in line with studies carried out in Lavapiés (Moustaoui-Srhir, 2018;Saiz de Lobado, 2021;Saiz de Lobado and Revilla, 2019), as well as in other territories with similar characteristics (Ben-Rafael and Ben-Rafael, 2015;Vandenbroucke, 2018).…”
Section: Introduction and Objectivessupporting
confidence: 80%
“…These samples originally intended to analyse the presence of different ethnic minority groups in the territory. However, data suggested that the LC might not have only recorded traces of multilingualism, but also traces of the complex process of gentrification, in line with studies carried out in Lavapiés (Moustaoui-Srhir, 2018;Saiz de Lobado, 2021;Saiz de Lobado and Revilla, 2019), as well as in other territories with similar characteristics (Ben-Rafael and Ben-Rafael, 2015;Vandenbroucke, 2018).…”
Section: Introduction and Objectivessupporting
confidence: 80%
“…Whilst these differences may have an impact on the structure and the nature of the data, it should be noted that the two research projects that inform this analysis were not designed to examine the sociolinguistic consequences of urban regeneration (cf. Papen 2012; Trinch & Snajdr 2016; Baro 2017; Goncalves 2018; Vandenbroucke 2018). However, given the dramatic changes to East London and the perceived impact of urban regeneration on those who reside in the area, it is notable that these themes emerge in the everyday conversations of these communities.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst there is a growing body of research on discourses of gentrification (e.g. Baro 2017; Goncalves 2018; Vandenbroucke 2018), much less work has examined the ways in which young people relate to and experience changes in the urban environment (Howarth 2002; Butcher & Dickens 2016). Nevertheless, as a demographic who have little control over the displacement and precarity caused by gentrification (Watt 2013; Butcher & Dickens 2016), it seems necessary to explore the perspectives of youth and young adults (Butcher & Thomas 2003).…”
Section: Gentrification and Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Zhang () and Dong () both document how conspicuous consumption mediated by discourse serves as a foundation for an emerging middle‐class identity in contemporary China. Other studies explore the discourse of consumer‐oriented class identities within specific domains of materiality, such as food (Järlehed and Moriarty ; Karrebæk, Riley, and Cavanaugh ; Mapes ) and gentrification of urban spaces (Järlehed, Nielsen, and Rosendal ; Vandenbroucke ).…”
Section: Shifts In the Political Economymentioning
confidence: 99%